Credibility Perception of Viewers and Brand Equity: A Case Study of Private News Channels in Karachi - Chishti, Talha; ur Rahman, Mustaghis (JISR management and social sciences & economics, 2010)
This research studies the key indicators of brand credibility of a selected number of private news channels and aims to reveal the association of brand credibility with the brand equity of these channels. Four private news channels reaching at national level with wide area coverage on cable TV across the country were selected for this study. This is a quantitative study that applies regression analysis to test the formulated hypothesis. The study tests the existence of any association between brand credibility and brand equity of private news channels. Results indicate that fairness and unbiasness of a news channel is a moderate predictor for its high level of brand equity. Furthermore results also indicate that trust in the news channel is a stronger predictor for a high level of brand equity of the channel. The results thus allow the researcher to reject the null hypothesis and accept the alternate hypothesis formulated for this study.